Polyphase Tectonic Evolution of the Puerto Rico‐Virgin Islands Microplate Revealed by Fault‐Slip Data and Stress Inversions - Jean‐Claude Hippolyte; Paul Mann (Geochemistry, Geophysics, Geosystems)
Abstract The northeastern Caribbean plate boundary (NCPB) includes the Puerto Rico‐Virgin Islands (PRVI) microplate that is bounded by oblique subduction zones in the Muertos and Puerto Rico Trenches, and by the Mona Rift, and the Anegada Passage rifts. Over the past 40 years, a variety of tectonic models have been proposed for the evolution of this complex plate boundary. We analyze fault kinematic data from 57 outcrops of Oligocene to Pliocene sedimentary rocks in Puerto Rico, Vieques, and St. Croix to shed light on the geodynamic evolution of the PRVI microplate and the Anegada Passage. Fault kinematic data reveal that the Eocene‐Early Oligocene islands arc collision was followed by two contrasting extensional stress fields that occurred during and after the counterclockwise rotation of the PRVI microplate. Phase 1 compressional deformation related to Paleogene collision between the Caribbean arc and Bahama Platform was followed by: (a) Miocene, north‐northeast‐trending extension of tectonic Phase 2 resulting from counterclockwise rotation of the PRVI microplate; and (b) post‐rotation, Pliocene‐Quaternary, east‐west to northwest‐southeast extension of Phase 3. We propose that the Mona‐Yuma rift system and the South‐Puerto Rico‐Anegada systems, characterized by different extensional directions, form two independent tears in the NCPBZ generated by its post‐rotation left‐lateral shearing. Southeastward extension reactivates the Anegada Passage with slightly oblique extension and produces left‐lateral transtensional faulting along the southern margin of Puerto Rico. This active transtensional stress regime, documented in our previous studies, is confirmed by the moment tensors of the 2019–2023 earthquake sequence in southern Puerto Rico.